CO2 body worn logger - Leqele, Tumisang (Department of Electrical Engineering, 2016)
Tuberculosis is the second most killing disease in the world, although cure is being provided for the disease in South Africa, prevention becomes the most important part. This calls for a device which can be used to gather statistical data to be used in verifying where TB transmission mostly takes place, and proper conditions be implemented to minimise the TB transmission. Carbon dioxide Body Worn Device (CBWD) is a device which relies on the battery supply for its function. Its function includes gathering the CO2 level, humidity and Temperature as well as the location coordinates with time, and this data stored on the device memory, to allow for downloading, for the user to be able to analyse log data. The device stores its log data on the SD card, and its live results can be viewed using the software or on the device screen. A way to communicate with the device calls for a piece of software which the user can interact with as to issue commands to the device. CBWD software is a piece of software which provides the interface for the user to be able to interact with the device. It provides an easy user menu for the user to download log data, erase log data, synchronise device date and time, and zero the CO2 level. The software also provides the storage for last data downloaded for the device. The system can be improved to integrate with other devices as a control system, for instance on the ventilation system, the device can be integrated to regulate the ventilation rate factors based on the current conditions on the area.